Desempenho produtivo de ovinos terminados com dietas de alto concentrado contendo borra de babaçu - SOUSA, Maykon Nunes de (2020)
The objective of this study was to evaluate the inclusion of increasing levels of babassu sludge in the diet of finishing sheep. Four experimental diets with levels of babassu sludge (BS) were evaluated 0; 5; 10 and 15% of dry matter (DM). The experimental design was completely randomized using the initial weight as a covariate with four treatments and six repetitions. Consumption, digestibility, physiological parameters, performance and ingestive behavior were evaluated. 24 male sheep were used, crossbred, Santa Inês, castrated, with an average weight of 24.66 ± 4,06 kg and an average age of four months, which were confined for a period of 60 days. For data analysis, regression with a 5% significance level was used. An increasing linear effect was observed for dry matter (P = 0.0037), crude protein (P = 0.0351), ether extract (P = 0.0053), neutral detergent fiber (P <, 0001 ), organic matter (P = 0.0029), and total carbohydrates (P = 0.0053). The digestibility of organic matter behaved in a quadratic way (P = 0.0461). There was no statistically significant effect (P> 0.05) for feed conversion, feed efficiency and average daily weight gain. Water consumption showed no difference (P> 0.05) due to the increasing levels of BS. The inclusion of BS did not change (P> 0.05) the respiratory rate, heart rate, body temperature and rectal temperature, however, the feeding schedule influenced (P <0.05) all variables, except the cardiac frequency. There was a linear effect for the feed efficiency of the neutral detergent fiber (P = 0.0256), time of mericic chewing by ruminal cake (P = 0.0090), There was a quadratic effect for the variables rumination time (P = 0.0078), dry matter rumination efficiency (P = 0.0215), neutral detergent fiber rumination efficiency (P = 0.0369), cake ruminal (P = 0.0424), number of mericic chewing (P = 0.0026). The inclusion of babassu sludge in up to 15% in diets for finishing sheep fed with a high proportion of concentrate guarantees a performance similar to diets containing ground corn and soybean meal.